The relationship between alcohol use and risky sexual behaviour in South Africa - Magni, Sarah (My University, 2014)
Introduction: Alcohol is an indirect contributor to HIV transmission in sub-Saharan Africa. Alcohol users in general, and heavy, episodic drinkers in particular, are more likely to engage in risky sexual behaviour. Interventions promoting the reduction of alcohol use in conjunction with sex are likely to enhance the HIV prevention response. However, little is known about the relationship between different dimensions of alcohol use and risky sexual behaviour in the general adult population in South Africa. The overall aim of this study was to examine the relationship between alcohol dependence, binge drinking and frequency of drinking in the past month and risky sexual behaviour among males and females aged 16-55 years in South Africa in 2012. Methods: This was a secondary analysis of data from a nationally representative cross-sectional study of males and females aged 16-55 years in 2012. Bivariate and multivariate analysis was conducted to investigate the relationship between alcohol use and risky sexual behaviour. Three nuanced measures of alcohol use were used – alcohol dependence, binge drinking, and frequency of drinking in the past month. The outcomes examined included multiple sexual partners (MSP) in the past 12 months, MSP in the past month, transactional sex, age-disparate sex and condom use at last sex. Results: Some 10,034 respondents (n=4,065 males and n=5,969 females) were interviewed. This study found that for males, there was no significant relationship between alcohol dependence and risky sexual behaviour. For females, those who were alcohol dependent were more likely to have received money/gifts in exchange for sex. Binge drinking and frequency of drinking in the past month were associated with risky sexual behaviour for both males and females. For males, binge drinking was associated with: MSP in the past 12 months (AOR: 1.93, 95% CI 1.37 - 2.72), providing gifts/money in exchange for sex (AOR: 1.53, 95% CI 1.01 - 2.33), and having a sexual partner five or more years younger than themselves (AOR 1.44, 95% CI 1.09 - 1.89). An interaction between binge drinking and self-efficacy for resisting MSP was positively associated with MSP in the past month. Frequency of drinking in the previous month was associated with all five outcome variables and a dose response relationship was present. An interaction between frequency of drinking and self-efficacy for resisting MSP was positively associated with MSP in the past month. For females, binge drinking was associated with: MSP in the past 12 months (AOR 1.93, 95% CI 1.37-2.72), MSP in the past month (AOR 1.79, 95% CI: 1.03 - 3.10), and receiving money/gifts in exchange for sex (AOR 3.10, 95% CI 1.45 - 6.62). An interaction between binge drinking and self-efficacy for resisting MSP was positively associated with MSP in the 12 past months. Frequency of drinking was associated with MSP in the past month. A dose response relationship was evident with females who drank more frequently in the past month being more likely to have had MSP in the past 12 months. This study found high levels of non-drinking (62.80%) but high levels of hazardous drinking among those who drank. Males were more likely to drink and to display hazardous drinking patterns. In general males were more likely to engage in risky sexual behaviour, although males were more likely to have used a condom at last sex. Conclusions: Overall this study has described the patterns and prevalence of alcohol use and risky sexual behaviour in the general population in South Africa. It has demonstrated gender-specific relationships between various types of alcohol use and risky sexual behaviour and has new insights into the complex relationship between these two phenomena. Results suggest that the drinking environment facilitates high-risk sexual encounters. Findings from this study can be used to design and implement future interventions to address this important risk factor for HIV.
Keywords: Sexual Behavior--South Africa; Alcohol Drinking--adverse effects